Epidemiological profile of the population affected by dengue in Três Lagoas-MS: Analysis of epidemiological weeks 1 to 30 of 2023 - Silva, Mauro (2024)
Background: The city of Três Lagoas, in Mato Grosso do Sul, has a population of 132,000 inhabitants, and accelerated urban growth in recent years, resulting in socio-environmental and spatial planning problems. In recent years, several episodes of dengue outbreaks and epidemics have been recorded in the municipality. Thus, the research sought to understand the epidemiological profile of the population affected by Dengue in Três Lagoas in the period from January to July 2023. Methods: Data on the evolution of reported cases of dengue for the first 30 epidemiological weeks of 2023 were analyzed. The information was based on the “Investigation Sheets” of the Disease and Notification Information System – SINAN-NET, provided by the Municipal Health Department of Três Lagoas. The variables used for the epidemiological analysis were: incidence of cases; age group; gender; race, education, clinical data, and evolution. Results: The results showed that in epidemiological weeks 10 to 13, incidence rates evolved from 300 to levels above 600 reported cases of dengue for every 100 thousand inhabitants, with the most worrying period being in the first half of 2023 in Três Lagoas. It was also revealed that the main epidemiological characteristic of the population affected by dengue is that the majority of people are female, with a predominance of brown and black people aged between 19 and 60 years, but the elderly were those who most likely died. The main symptoms were fever, myalgia and headache.